Influence of manufacturing process on fatigue resistance of high strength steel bolts for connecting rods. (January 2020) - Acri, A.; Beretta, S.; Bolzoni, F.; Colombo, C.; Vergani, L.M.
Highlights: Connecting rod bolts are critical fasteners. Fatigue tests to highlight the effect of coatings (Mn-phosphate and micro Zn-phosphate) on fatigue performance. Analysis of hydrogen content, correlated to the manufacturing process. Fractographic investigation of crack initiation and propagation. Abstract: The connecting rod (or conrod) is an important component of an internal combustion engine. An eventual failure of the bolts clamping the big end of conrods can cause failure of the engine; for this reason, they are addressed as " critical fasteners ". Bolts manufacturers must guarantee steel purity and avoid any surface defects, thread forming laps, surface decarburization, surface phosphate diffusion or hydrogen embrittlement risk in order to increase their reliability. This paper is focused on coating treatments of bolts and on their effect on fatigue life. An experimental testing campaign has been performed to investigate the effect of Mn-phosphate coating and micro Zn- phosphate coating on fatigue performances of the bolts, compared with the not coated ones. Particular attention is paid to the surface preparation of the bolt (i.e. by acid pickling or sandblasting) before the final phosphate coating operation. Diffusible and total hydrogen has been measured on all the bolts to verify the possible influence of hydrogen embrittlement.